PENGARUH PENDIDIKAN CEO, DEWAN KOMISARIS DAN KOMITE AUDIT TERHADAP NILAI PERUSAHAAN (STUDI PADA SEKTOR BASIC MATERIAL TAHUN 2021 – 2023) - Arista Indah Sekar Ayu,; Hasnawati, Hasnawati (Journal of Innovation Research and Knowledge, 2025)
This research aims to analyze the influence of the education of the Chief Executive Officer (CEO), board of commissioners and audit committee on firm value. This research uses a quantitative approach with secondary data obtained from the annual reports of companies listed on the Indonesia Stock Exchange (BEI) during the 2021 - 2023 period. The independent variables in this research include the education level of the CEO, education and meeting of audit committee and meeting of board of commissioners. Meanwhile, the dependent variable is company value which is measured using Tobin's Q. In conducting this research, the author used a purposive sampling technique which selected samples based on characteristics that could support the independent variable. This research was conducted on 102 companies in the basic materials sector with 278 observations. The research results show that CEO education, board of commissioners and audit committee has a positive influence on firm value